Cardioneuroablation: the known and the unknown - Marrese, A.; Persico, R.; Parlato, E.; Faccenda, D.; Salucci, A.; Comparone, G.; Pergola, V.; Ammirati, G.; Addeo, L.; Fonderico, C.; Cocchiara, L.; Volpe, A.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Cardioneuroablation (CNA) is a novel interventional procedure for the treatment of recurrent vasovagal syncope (VVS) and advanced atrioventricular block secondary to hyperactivation of vagal tone in young patients. By damaging the cardiac parasympathetic ganglia, CNA seems to be able to mitigate and/or abolish the excessive vagal activity and improve patients’ outcome. This review is intended to give a detailed and comprehensive overview of the current evidences regarding (1) the clinical applications of CNA (2) the identification of ablation targets and procedural endpoints (3) the medium-long term effect of the procedure and its future perspectives. However, clinical data are still limited, and expert consensus or recommendations in the guidelines regarding this technique are still lacking.